Marine and other aquatic dermatoses - Jandhyala Sridhar; Rajeev Deo (Wolters Kluwer Medknow Publications, 2017)
Occupational and recreational aquatic activity predisposes our population to a wide variety of dermatoses. Sunburn, urticaria, jellyfish stings, and contact dermatitis to rubber equipment are common allergies that are encountered in the aquatic environment. Among the infections, tinea versicolor, intertrigo, and verruca vulgaris are widespread. Swimmer's itch may occur due to skin penetration by schistosome cercariae, while free-floating nematocysts of marine coelenterates may precipitate seabather's eruption. "Suit squeeze" due to cutaneous barotrauma and lymphoedematous peau d'orange due to decompression are rare, described entities. This review serves as a ready reckoner for Indian dermatologists and medical practitioners to identify and manage these conditions.